The relation between adult adoptees' feelings about relinquishment, adoption and satisfaction with life. (July 2019) - ter Meulen, Gera; Smeets, Daisy; Juffer, Femmie
Previous studies have revealed that despite adversity in early childhood, after adoption intercountry adoptees show a substantial catch-up in physical, socio-emotional and cognitive development and do relatively well in life. However, these favourable situations do not necessarily match positive views of their earlier experiences when recalled as adults. This study explores this relationship: namely adult adoptees' appraisal of relinquishment and adoption, and their satisfaction with life. It analyses questionnaire replies from 1155 adult intercountry adoptees in the Netherlands, originating from 32 countries and now aged between 18 and 55. Their mean age at the time of the research was 29 and they had arrived in the Netherlands at an average age of 1.34 years. It was found that the respondents were mostly satisfied with their lives, even more so than the wider Dutch population. Moreover, the more positive their feelings about relinquishment and adoption the higher the levels of life satisfaction. Most adoptees felt positive about being adopted although a minority (about 10%) often had negative feelings about adoption. The majority indicated that they had become more satisfied with their adoption status as they grew older; however, those who were older at the time of the study were less happy with this and also less satisfied with their lives in general. This probably reflects improvements in adoption practice since the 1990s, in particular the provision of good quality pre- and post-adoption support services. These findings highlight the value of therapeutic work with adoptees that includes a focus on their feelings about both relinquishment and adoption, with the expectation that this will improve their well-being and life satisfaction.